1991
DOI: 10.1017/s0266462300012472
|View full text |Cite
|
Sign up to set email alerts
|

CPAP and Mechanical Ventilation

Abstract: Respiratory insufficiency has previously been a frequent cause of neonatal death, especially in preterm infants. As late as in 1967, Silverman and associates (66) found that in infants with hyaline membrane disease (HMD), mechanical ventilation with a body-enclosing negative pressure respirator did not improve survival. Before 1970, the mortality among infants who required respiratory therapy was high (20;46;70). At the end of the 1960s and the beginning of the 1970s, several new methods were introduced to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…Therefore, an infant requiring low FiO 2 has higher lung compliance and needs less CPAP. Clinical observations, however, have indicated that some preterm infants require nasal-CPAP for some time after their FiO 2 requirements have reached atmospheric levels (9,10), and in Rigshospitalet the tradition is, in general, not to decrease CPAP pressure below 4 cmH 2 O. In the present trial, oxygenation variables dropped after discontinuation of CPAP.…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, an infant requiring low FiO 2 has higher lung compliance and needs less CPAP. Clinical observations, however, have indicated that some preterm infants require nasal-CPAP for some time after their FiO 2 requirements have reached atmospheric levels (9,10), and in Rigshospitalet the tradition is, in general, not to decrease CPAP pressure below 4 cmH 2 O. In the present trial, oxygenation variables dropped after discontinuation of CPAP.…”
Section: Discussioncontrasting
confidence: 48%
“…This carried significant risks and had considerable resource implications, particularly the need for specially trained staff to care for the patient and the need for expensive ventilatory and monitoring equipment, usually only available in intensive care units (ICU), In Australia, mechanical ventilation is unlikely to be offered to patients aged over 85 years while practice for those aged 80 to 85 years varies. CPAP therapy by face mask has been suggested as an alternative adjunctive therapy in the treatment of APO 1,2,5–8 and has shown to be effective 3,4,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Continuous positive airway pressure can also increase the work of breathing (2;11). Technical aspects of continuous positive airway pressure are further discussed by Sedin (26).…”
Section: Indications For Continuous Positive Airway Pressure and Respmentioning
confidence: 99%